Os três momentos pedagógicos e a elaboração de problemas de Física pelos estudantes - MARENGÃO, Leonardo Santiago Lima (2012)
In this study we investigated the possibility of students identify problems in physics in their daily lives after they have classes of Mechanics under the dialogical process of questioning, through the Three Pedagogical Moments. The survey was conducted with students of the night course of Technician Cargo Transportation, in the form PROEJA from Federal Institute of Goias - Annapolis Campus. Data collection occurred in two stages: first were applied to all students‟ questionnaires consisting of open questions and then were held semi-structured interviews with some of these students. Throughout the development stages of the Three Moments students draw up proposed Pedagogical problems in physics. The interpretation of the questionnaire responses and interview transcripts through the content analysis suggests that the development of the Three Pedagogical Moments with the development of problems by the students, allows for a relative ownership of such problems by themselves, which helps them develop an awareness of the presence of physics in situations of everyday life, yet they demonstrate conceptual difficulties. The dialogical approach the teacher and the students' active participation throughout the process were also key features to which students were able to build physics problems outside the school environment.